Young EFL Learners Collaboratively Writing a Dialogue During a Regular Classroom Lesson - Kos, Tomas (International Journal of English Studies, 2023)
A growing body of research has explored collaborative writing (CW) among young learners. Nevertheless, studies have mainly focused on tasks such as the dictogloss, which is rather uncommon in regular classroom teaching and has neglected activities that are more common. In addition, research has focused on language-related episodes (LREs) without considering other important episodes including those that involve the teacher. Finally, only one study has explored to what extent the decisions made within LREs transfer into the written product. With these research gaps in mind, the present study examined CW of 12 pairs composed of 10 to 11-year-old learners of English as a foreign language (EFL) who jointly wrote a role-play. Drawing on audio recordings of pair work interactions and documentary analysis of students’ written work, the study has found that in addition to LREs, students frequently engaged in content-related and activity-related episodes with the teacher’s involvement being rather limited. Despite the teacher’s presence, a high proportion of LREs was resolved incorrectly or left unresolved. Nearly all correctly and incorrectly resolved LREs were also incorporated into the jointly written role-play. Students focused predominantly on the language targeted by the activity (lexical phrases) and attended to other language aspects minimally.